Desarrollo de un software para el monitoreo de pérdidas de producción en los campos Platino y Eva ubicados en las cuencas Caguán-Putumayo y Valle superior del Magdalena respectivamente (2017)
In the following work are presented the aspects related to the design of a software to improve the management performed on the daily production losses with respect to the potential of each well or deferred, which allows the increase of income for the company. Initially it refers to all the general features that influence production operations for the Platinum and Eva Fields, from which the causes of the problems are taken and are characterized, to make it part of the software as input data. Afterwards, the software design, development and operation are explained, taking into account all the information covered by it, establishing the input and output variables and the generation of reports as the primary objective of the application. Finally, a financial analysis is presented, in which is studied the viability of its implementation in the corresponding area of the company, through the value indicator Net Present Value (NPV).